2023
DOI: 10.1093/europace/euad017
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein isolation with the radiofrequency balloon catheter: a single centre prospective study

Abstract: Aims The multielectrode radiofrequency balloon catheter (RFB) has been developed to achieve safe and effective pulmonary vein isolation (PVI) for atrial fibrillation (AF) ablation. This single-centre study aimed to evaluate the midterm clinical outcome and predictors of single-shot PVI with the novel RFB. Methods and results All consecutive patients with symptomatic paroxysmal or persistent AF undergoing first-time PVI with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
4
25
2
Order By: Relevance
“…The consensus on antiarrhythmic treatment strategies, particularly the widespread use of CA, 23 , 24 suggests a strong preference for rhythm control in AiCM, aligning with recent data 19 , 25–28 and current guidelines recommending CA as a first-line treatment when AiCM is highly probable independent of symptom status (class I, level of evidence B, ESC Guidelines). 29 , 30…”
Section: Discussionmentioning
confidence: 64%
“…The consensus on antiarrhythmic treatment strategies, particularly the widespread use of CA, 23 , 24 suggests a strong preference for rhythm control in AiCM, aligning with recent data 19 , 25–28 and current guidelines recommending CA as a first-line treatment when AiCM is highly probable independent of symptom status (class I, level of evidence B, ESC Guidelines). 29 , 30…”
Section: Discussionmentioning
confidence: 64%
“…The incidence of persistent diaphragm paralysis was 0.7%, the risk being increased in womens. In a recent prospective, multicenter study conducted in 375 subjects comparing cryoballoon to radiofrequency, data showed that cryoablation has the highest level of phrenic nerve injury with 7.20% transient paralysis compared to 3.20% for radiofrequency[ 21 ]. Today, a new non-thermal energy modality, called pulse field ablation (PFA) therapy has emerged.…”
Section: Diaphragm Dysfunction Induced By Atrial Fibrillation Ablationmentioning
confidence: 99%
“…It is generated at a frequency of 500–1,000 KHz and transmitted between the catheter tip and a skin patch. Even if RF single-shot catheters are currently available ( 29 ), RF is mostly delivered with a point-by-point approach. However, this technique is demanding and associated with a long learning curve.…”
Section: Pulmonary Veins Isolation: Techniques Technologies and Energ...mentioning
confidence: 99%